2010
DOI: 10.4209/aaqr.2009.10.0068
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Sources of Carbonaceous, Ionic, and Isotopic Species of Wintertime Atmospheric Aerosols in Kathmandu Valley, Nepal

Abstract: To investigate the air pollution from aerosols in Kathmandu during winter, bulk aerosol samples were collected during winter [2007][2008] to characterize carbonaceous and ionic species and carbon and nitrogen isotopes. This study illustrates the applications of carbon and nitrogen isotope data for characterizing aerosols and their implications for identifying sources that were inconsistent with the results for the carbonaceous and ionic aerosols. Mean concentrations of organic carbon (OC), elemental carbon (EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 47 publications
4
41
1
Order By: Relevance
“…Previous studies on particulate chemical composition, including carbonaceous aerosols, ions/ metals, and PAHs, have suggested that the atmospheric composition in the Kathmandu Valley is considerably influenced by anthropogenic emissions from sources such as vehicles, industries, and biomass burning, and even the long-range transportation of pollutants from the Indian subcontinent (Kishida et al, 2009;Shakya et al, 2010;Tripathee et al, 2014).…”
Section: Tsp and Pah Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on particulate chemical composition, including carbonaceous aerosols, ions/ metals, and PAHs, have suggested that the atmospheric composition in the Kathmandu Valley is considerably influenced by anthropogenic emissions from sources such as vehicles, industries, and biomass burning, and even the long-range transportation of pollutants from the Indian subcontinent (Kishida et al, 2009;Shakya et al, 2010;Tripathee et al, 2014).…”
Section: Tsp and Pah Concentrationsmentioning
confidence: 99%
“…C values of aerosols in Kathmandu have also indicated that local vehicular emissions were a major source of pollutants (Shakya et al, 2010). In addition, PM 10 emissions from vehicular activities and industrial sources in Kathmandu constituted approximately 62% and 17% of the total PM 10 emissions, respectively (ICIMOD, 2007).…”
mentioning
confidence: 99%
“…Limited information exists for PM 2.5 (particles smaller than 2.5 µm in diameter) pollution (Aryal et al, 2009;Gurung and Bell, 2012; in this location, and even less information is available for PM chemical composition in the valley (Shakya et al, 2010;Chen et al, 2015). As developing nations continue to grow economically and societally, they are likely to be faced with critical decisions on energy consumption, transportation infrastructure, and public health protection measures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to emissions from vehicles and resuspended road dust due to vehicles, emissions from more than 100 brick kilns, the widespread use of small captive power generators during scheduled power cuts, and burning household and/or municipal wastes are other major sources of air pollution in the valley (ICIMOD, 2007;Shakya et al, 2010;The World Bank, 2014;Kim et al, 2015). The Kathmandu Valley has been facing rapidly deteriorating air quality on a metropolitan scale resulting from rapid urbanization and modernization, high population growth, the increasing number of vehicles, and increasing fuel consumption throughout the region.…”
Section: Introductionmentioning
confidence: 99%
“…Among the major sources of aerosol, emissions from agricultural-waste and biomass burning dominate during the wintertime (Dec-Feb) (Venkataraman et al, 2005;Rengarajan et al, 2007;Gustafsson et al, 2009;Ram et al, 2010a;Shakya et al, 2010;Rajput et al, 2011;Ram and Sarin, 2011). The transport of mineral aerosol from arid and semiarid regions of western India, during the summer (Aprilearly June), imparts strong temporal variability in the chemical composition and optical properties of aerosol (Jethva et al, 2005;Chinnam et al, 2006).…”
Section: Introductionmentioning
confidence: 99%